2007
DOI: 10.1124/dmd.107.017533
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Lithocholic Acid by Rat Hepatic Microsomes: Metabolite Analysis by Liquid Chromatography/Mass Spectrometry

Abstract: ABSTRACT:Lithocholic acid is a lipid-soluble hepatotoxic bile acid that accumulates in the liver during cholestasis. A potential detoxification pathway for lithocholic acid involves hydroxylation by hepatic cytochrome P450 (P450) enzymes. The purpose of the present study was to identify the hepatic microsomal metabolites of lithocholic acid by liquid chromatography/mass spectrometry and to determine the P450 enzymes involved. Incubation of lithocholic acid with rat hepatic microsomes and NADPH produced murideo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…A fixed amount (0.4 g) of murideoxycholic acid, which was the internal standard, was then added to each sample. Sample extraction, evaporation, and reconstitution in preparation for analysis by LC/MS were carried out as described previously (Deo and Bandiera, 2008). Reaction mixtures that were devoid of substrate, NADPH, or microsomes, as well as reaction mixtures that contained defined concentrations of authentic bile acid standards, were routinely included in each assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fixed amount (0.4 g) of murideoxycholic acid, which was the internal standard, was then added to each sample. Sample extraction, evaporation, and reconstitution in preparation for analysis by LC/MS were carried out as described previously (Deo and Bandiera, 2008). Reaction mixtures that were devoid of substrate, NADPH, or microsomes, as well as reaction mixtures that contained defined concentrations of authentic bile acid standards, were routinely included in each assay.…”
Section: Methodsmentioning
confidence: 99%
“…Formation of chenodeoxycholic acid and cholic acid metabolites was analyzed by LC/MS using a procedure described previously for lithocholic acid metabolites (Deo and Bandiera, 2008), with the following modifications. Chenodeoxycholic acid and cholic acid metabolites were detected using a Waters Acquity Ultra Performance Liquid Chromatograph System (UPLC, Waters, Milford, MA) consisting of a Binary Solvent Manager and Sample Manager and connected to a Waters Quattro Premier XE triple quadrupole mass spectrometer (Waters).…”
Section: Methodsmentioning
confidence: 99%
“…Internal standard (cholic-2,2,4,4-d 4 acid, 0.4 g) was then added to each sample. Sample extraction, evaporation, and reconstitution in preparation for analysis by LC/MS were carried out as described previously (Deo and Bandiera, 2008a). Reaction mixtures that were devoid of substrate, NADPH, or microsomes, as well as reaction mixtures that contained defined concentrations of authentic bile acid standards, were routinely included in each assay.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, a different metabolite, 3-oxo-5␤-cholan-24-oic (3-ketocholanoic) acid, was identified as the major product of lithocholic acid following incubation with human recombinant CYP3A4 (Bodin et al, 2005). Using rat liver microsomes, we showed that lithocholic acid was extensively metabolized by multiple P450 enzymes to six metabolites (Deo and Bandiera, 2008a). The predominant pathway involved 6␤-hydroxylation and produced murideoxycholic acid as the major metabolite.…”
mentioning
confidence: 99%
See 1 more Smart Citation